2017
DOI: 10.1016/j.seizure.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Stress as a seizure precipitant: Identification, associated factors, and treatment options

Abstract: Stress is a common and important seizure precipitant reported by epilepsy patients. Studies to date have used different methodologies to identify relationships between epilepsy and stress. Several studies have identified anxiety, depression, and childhood trauma as being more common in patients with epilepsy who report stress as a seizure precipitant compared to patients with epilepsy who did not identify stress as a seizure precipitant. In one survey study it was found that a majority of patients with stress-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Although others have acknowledged this relationship 19 , we must exert some hesitation with the underlying interpretation of our results. For example, the potential for bias in our results cannot be discounted, as the finding that the protective effect of farm use of nitrogen fertilizers against hospitalization for epilepsy may be associated with a more rural lifestyle that is less afflicted by stress, a recognized trigger for epilepsy 28 . However, this explanation is not consistent with our prior work showing a disproportionate burden in hospitalization for other mental health comorbidities, like ADHD (1997ADHD ( -2006, that occurs in these less populated areas, as we have discussed 7,9 .…”
Section: Discussionmentioning
confidence: 93%
“…Although others have acknowledged this relationship 19 , we must exert some hesitation with the underlying interpretation of our results. For example, the potential for bias in our results cannot be discounted, as the finding that the protective effect of farm use of nitrogen fertilizers against hospitalization for epilepsy may be associated with a more rural lifestyle that is less afflicted by stress, a recognized trigger for epilepsy 28 . However, this explanation is not consistent with our prior work showing a disproportionate burden in hospitalization for other mental health comorbidities, like ADHD (1997ADHD ( -2006, that occurs in these less populated areas, as we have discussed 7,9 .…”
Section: Discussionmentioning
confidence: 93%
“…Although results from the general public suggested that stress would increase the risk of epileptogenesis, especially in childhood, 38 the relationship between seizure onset of patients with epilepsy and stress was evaluated through different methods. The different results may come from potential confounders between stress and mental status, 39 such as bad habits under pressure, and patients' use of a stress reduction method if they feel stress triggers their seizures. 40 Whether our patients received multior monotherapy also did not influence this risk, consistent with the reported lack of association between multi-or monotherapy and prevalence of depression or anxiety among patients with epilepsy.…”
Section: K-6 Item Patients With Epilepsymentioning
confidence: 99%
“…The figure highlights both discrete and overlapping temporal domains of these mediators, as well as their time-dependent actions on the network itself. Importantly, this type of temporal evolution is difficult to ascertain in human studies, which are typically based on questionnaires [26, [7173]. In the aggregate, human studies implicate both acute and chronic stress, occurring over time-periods ranging from hours to weeks, as a seizure-promoting factor in people with epilepsy [7176].…”
Section: The Temporal Aspects Of the Functions Of Stress-mediators Inmentioning
confidence: 99%